2004
DOI: 10.1007/s10344-004-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and allometric studies on eggshells and embryos of free-living Canada geese (Branta c. canadensis Linnaeus, 1758)

Abstract: A total of 289 eggs laid by free-living Canada geese (Branta canadensis canadensis Linnaeus, 1758) in the northwestern part of Germany were collected in spring 2002 and 2003 and examined for shell and embryo parameters. Mean egg mass was 160.88±19.68 g. Approximately 90% of all eggs had a mass between 140 and 185 g. About 90% of all clutches consisted of four to seven eggs. The form index of 90% of all eggs was in the range 62-74. The mean eggshell thickness on the blunt pole was 0.52±0.08 and 0.53±0.07 mm on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…These structures within the pore canal were seen in samples before incubation, so we considered that they were a feature of goose species and related to the strength of the eggshell and they were not related to the incubation period. Bönner et al [26] reported that the thickness of average of goose eggshell was 530 µm, Gualhanone et al [27] stated that the thickness of average of chicken eggshell was 370 µm and Yamak et al [28] informed that the thickness of average of chicken eggshell was 380 µm. In this study, there was a big difference between the thickness of average of goose eggshells and that of chicken so we compared the thickness of an BİNGÖL, DEPREM, KARADAĞ SARI KORAL TAŞÇI, ASLAN average eggshell statistically among the groups within each species.…”
Section: Discussionmentioning
confidence: 99%
“…These structures within the pore canal were seen in samples before incubation, so we considered that they were a feature of goose species and related to the strength of the eggshell and they were not related to the incubation period. Bönner et al [26] reported that the thickness of average of goose eggshell was 530 µm, Gualhanone et al [27] stated that the thickness of average of chicken eggshell was 370 µm and Yamak et al [28] informed that the thickness of average of chicken eggshell was 380 µm. In this study, there was a big difference between the thickness of average of goose eggshells and that of chicken so we compared the thickness of an BİNGÖL, DEPREM, KARADAĞ SARI KORAL TAŞÇI, ASLAN average eggshell statistically among the groups within each species.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it has been determined that there is a low correlation between the shape index of Branta canadensis goose eggs and embryo sex [10].…”
Section: Pre-incubation Methodsmentioning
confidence: 99%
“…In addition, in [14], a data set of various geometric parameters of 3313 eggs taken from 51 species of wild birds was subjected to statistical analysis and it was concluded that it was impossible to determine the sexual dimorphism of a bird egg by its geometric parameters. Despite similar studies of a batch of 289 Canadian goose eggs carried out in [13], where the possible influence of the shape index on the sex of embryos is assumed, it can be concluded from the literature that there is no correlation between sexual dimorphism and the geometric parameters of bird eggs.…”
Section: Problem Definitionmentioning
confidence: 96%
“…It should be noted that this indicator is different for the species, subspecies, chicken cross, and also depends on other factors [11][12][13]. In addition, in [14], a data set of various geometric parameters of 3313 eggs taken from 51 species of wild birds was subjected to statistical analysis and it was concluded that it was impossible to determine the sexual dimorphism of a bird egg by its geometric parameters.…”
Section: Problem Definitionmentioning
confidence: 99%